Climate value of energy storage for floating photovoltaic across China’s decarbonizing power grids - Ran Hao; Xin Sun; Yuchen Zhao; Chengchao Huang; Lili Yang; Weiqiao Wang; Junyu Sun; Li Fei; Lihao Zhao (ENGINEERING Environment, 2026)

Recent advances in therapeutic agents for uranium poisoning: a comprehensive review - Juan Li; Wenrun Li; Feng Huang; Qiuchi Wang; Hongjia Liu; Liyi Chen; Qiuping Wang; Yong Li; Shiyan Fu; Yazhen Zhao; Yonghong Ran; Yuhui Hao (BioMetals, 2026)

A lyophilized CHA–lateral flow platform for point-of-care detection of miR-106b-5p from L1CAM-Immunocaptured small extracellular vesicles in Alzheimer's disease - Ran Xu; Hao Chen; Chao Zhao; Xiqing Ding (Analytica Chimica Acta, 2026)

Probiotic Bacillus strains enhance cellulose digestibility and silkworms growth via gut microbiota modulation - Yueqin Jin; Ying Zhao; Chen Chen; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

pH-responsive metal–organic framework–iron scaffolds for antibacterial and osteogenesis-promoting applications in diabetic infected bone defects - Yaxin Xue; Xinyu Ran; Danyang Zhao; Jian Wang; Hao Jiang; Chengji Wang; Wei Xu; Hao Lv; Zhencheng Yu; Zijing Du; Yi Cao; Dongmei Dong; et al. (Chemical Engineering Journal, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

Genomic insights into marine-freshwater transition: evolutionary adaptations in freshwater Pusa seals - Liang Zhao; Hao Yu; Xinyue Yang; Inge Seim; Ran Tian (Genetica, 2026)

Joule heating-driven chemical looping dry reforming of CH4 and CO2 over monolithic LaFeO3/Ti wire oxygen carrier - Kun Wang; Haoyu Qi; Shengnan Zhao; Zezhou Ran; Hao Zhang; Kunlun Li (Chemical Engineering Journal, 2026)

A self-perpetuating cycle: how heavy metals shape DOM chemistry to promote their own immobilization in soil - Shuyi Zhang; Wenjun Zhang; Ye Li; Longfei Zhao; Chunmei Ran; Hongming Cai; Zhineng Hao; Junjie Zhang; Lei Wang (Environmental Monitoring and Assessment, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Long-term capsaicin intake and gut inflammation: microbial alterations, metabolic mechanisms, and intervention effects - Liangliang Zhu; Yijia Chen; Jiayang Jin; Mengyao Zhao; Jingfang Ran; Hao Yin; Xiaoguo Ji; Liming Zhao (Food Research International, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

AnchorReF: A novel anchor-based visual re-localization framework aided by multi-sensor data fusion - Hao Wu; Yu Ran; Xiaoxiang Zhang; Xinying Luo; Li Wang; Teng Zhao; Yongcheng Song; Zhijun Zhang; Huisong Zhang; Jin Liu; Jian Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Exploration of the pathway and mechanism of phycocyanin accumulation: A review - Xiaoxuan Zhou; Zhengdong Wan; Ran Gao; Jianxiong Hao; Wei Wang; Xuechao Zheng; Dandan Zhao (Bioresource Technology Reports, 2026)

Depleted uranium exposure induced ferroptosis in renal cells via the ETHE1/P38-MAPK pathway - Feng Huang; Wenrun Li; Juan Li; Yonghong Ran; Shiyan Fu; Li Shen; Qi Li; Xiaoyu Yang; Yazhen Zhao; Yuhui Hao (Archives of Toxicology, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Effects of chronic social defeat stress on behavior and cognition by activating the ERS-NLRP3 signaling pathway in adult mice - XiaoLei Gao; Ran Hao; ZengYun Jing; GuangBiao Huang; Lina Wang; Anna Ma; ZhaoHui Zhang; Tong Zhao (Metabolic Brain Disease, 2025)

Highly selective electrocatalytic H2O2 generation catalyzed by cobalt- and nitrogen-modified molybdenum carbide in acidic electrolyte - Ran Mao; Shen Zhao; Zhen Wei; Jingwei Hao; Weiyue Dang; Haimin Zhang; Xu Zhao (Chemical Engineering Journal, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Machine learning decoding of electronic thresholds in prediction of oriented generation of solar-induced oxidative reactive species and antibiotics degradation - Hao Bi; Zhiruo Zhou; Qian Liu; Ran Zhao; Fangyuan Chen; Jun Zhang; Zhurui Shen (Journal of Hazardous Materials, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

Corrigendum to “Chronic oral depleted uranium leads to reproductive damage in male rats through the ROS-hnRNP A2/B1-COX-2 signaling pathway” [Toxicology 449 (2021) 152666] - Binghui Lu; Yonghong Ran; Shuang Wang; Juan Li; Yazhen Zhao; Xinze Ran; Rong Li; Yuhui Hao (Toxicology, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Integrating allocation methods and regional optimization in life cycle assessment of floating photovoltaics for cleaner energy transitions in China - Ran Hao; Xin Sun; Yuchen Zhao; Jiahang Shang; Xue Zhu; Hongwei Li; Fengling Liu (Journal of Cleaner Production, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Corrigendum to “Biomimetic polydopamine nanoassembly regulates M2 macrophage polarization to alleviate radiation-induced pulmonary fibrosis via the PI3K/AKT/S100A4 pathway” [Chem. Eng. J. 506 (2025) 159980] - Li Shen; Shiyan Fu; Wenrun Li; Kuan Yu; Yonghong Ran; Guangyou Shi; Huanhuan Tan; Feng Huang; Qi Li; Yong Li; Yazhen Zhao; Xinze Ran; et al. (Chemical Engineering Journal, 2025)

Correction: Mitigation of depleted uranium-induced mitochondrial damage by ethylmalonic encephalopathy 1 protein via modulation of hydrogen sulfide and glutathione pathways - Juan Li; Yong Li; Yazhen Zhao; Suiyi Liu; Wenrun Li; Huanhuan Tan; Li Shen; Yonghong Ran; Yuhui Hao (Archives of Toxicology, 2025)

Optimizing push-flow aeration in urban shallow lakes: Threshold-based algal control and nutrient dynamics through field-validated numerical modeling - Xin Sun; Jiahang Shang; Lihao Zhao; Hongwei Li; Ran Hao (Journal of Water Process Engineering, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

The role and function mechanism of pilV in modulating the pathogenicity of Aeromonas hydrophila - Zhengshi Zhang; Jiayan Ran; Shengfu Zhao; Hui Luo; Shuqing Zheng; Detao Li; Ziyang Li; Yongyao Yu; Hao Xu; Ronghua Wu; Hua Ye (Aquaculture, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Surface-complexation-directed selective oxidation of phosphonates by decoration of copper anchoring sites - Hao Wang; Zixuan Zeng; Ran Duan; Hua Sheng; Chao Shan; Wenjing Song; Jincai Zhao (Chemical Engineering Journal, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

Mitigation of depleted uranium-induced mitochondrial damage by ethylmalonic encephalopathy 1 protein via modulation of hydrogen sulfide and glutathione pathways - Juan Li; Yong Li; Yazhen Zhao; Suiyi Liu; Wenrun Li; Huanhuan Tan; Li Shen; Yonghong Ran; Yuhui Hao (Archives of Toxicology, 2025)

The time-stamped effects of screen exposure on food intake in adults: A meta-analysis of experimental studies - Jing Bai; Hao Zhu; Xiaowen Ran; Haiyan Qu; Li He; Yang Zhao (Appetite, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Biomimetic polydopamine nanoassembly regulates M2 macrophage polarization to alleviate radiation-induced pulmonary fibrosis via the PI3K/AKT/S100A4 pathway - Li Shen; Shiyan Fu; Wenrun Li; Kuan Yu; Yonghong Ran; Guangyou Shi; Huanhuan Tan; Feng Huang; Qi Li; Yong Li; Yazhen Zhao; Xinze Ran; et al. (Chemical Engineering Journal, 2025)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Promotion strategy of low-carbon multimodal transportation considering government regulation and cargo owners’ willingness - Xinghua Hu; Ruizi Cheng; Jiahao Zhao; Ran Wang; Tingting Zhang; Hao Lei; Ba Liu (Environment, Development and Sustainability, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Exploration of risk analysis and elimination methods for a Cr(VI)-removal recombinant strain through a biosafety assessment in mice - Wanting You; Qiuying An; Dongbei Guo; Zebo Huang; Lulu Guo; Zigui Chen; Hao Xu; Guangshun Wang; Yeting Weng; Zhangye Ma; Xiaoxuan Chen; Feng Hong; et al. (Science of The Total Environment, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

A two-stage approach to siting electric bus charging stations considering future-current demand - Xinghua Hu; Hao Lei; Dongde Deng; Yuhang Bi; Jiahao Zhao; Ran Wang (Journal of Cleaner Production, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Preliminary assessment of carbonic acid dissociation constants: Insights from observations in China's east coastal oceans - Ping Wang; Qicheng Meng; Liang Xue; Yuhang Zhao; Hao Qiao; He Hu; Qinsheng Wei; Ming Xin; Xiangbin Ran; Chenhua Han; Feng Zhou; Chunying Liu (Marine Environmental Research, 2023)

Recovery of carbon from spent carbon cathode by alkaline and acid leaching and thermal treatment and exploration of its application in lithium-ion batteries - Hao Zhou; Dayong Zhang; Yongjun Jiang; Bo Zeng; Chenxi Zhao; Mingjie Zhang; Baiyan Zeng; Xiaoquan Zhu; Xintai Su; Valentin Romanovski; Ran Bi (Environmental Science and Pollution Research, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Mapping cropland suitability in China using optimized MaxEnt model - Xiaoliang Li; Kening Wu; Shiheng Hao; Zhang Yue; Zhao Ran; Jinliang Ma (Field Crops Research, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Mapping of suitable habitats for earthworms in China - Xiaoliang Li; Kening Wu; Shiheng Hao; Long Kang; Jinliang Ma; Ran Zhao; Yue Zhang (Soil Biology and Biochemistry, 2023)

Depleted uranium induces thyroid damage through activation of ER stress via the thrombospondin 1-PERK pathway - Chang Shu; Jie Li; Suiyi Liu; Yong Li; Yonghong Ran; Yazhen Zhao; Juan Li; Yuhui Hao (Chemico-Biological Interactions, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Nitrogen Alleviated the Deterioration of Rice Quality by Affecting the Accumulation of Grain Storage Protein Under Elevated Temperature - Yufei Zhao; Xuan Ran; Tongyang Yin; Hao Guo; Xiaoyang Zhang; Yingying Shen; Wenzhe Liu; Yanfeng Ding; She Tang (Journal of Plant Growth Regulation, 2023)

Efficient oxidation of ammonium to nitrogen gas via accelerated ClO• generation at TiO2/Ru-IrO2 bifacial electrode in a UV-driven photoelectrochemical system - Yi Liu; Ran Mao; Jingwei Hao; Kaifeng Wang; Ke Hu; Yuexin Cui; Xu Zhao (Chemical Engineering Journal, 2023)

Molten NaCl assisted pyrolysis of ZIF-8/PAN electrospun fibers to synthesis 1D cross-linked mesoporous N-rich carbon as oxygen reduction electrocatalysts - Shuai Ran; Ji Qi; Xufeng Dong; Hao Huang; Min Qi; Wenjing Dong; Penghui Zhao; Zenghui Zhao; Jingyuan Yang (Chemical Engineering Journal, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Sustainable utilization of residual grass: effect of anaerobic storage days on chemical composition, fermentation performance, microbial community, and functional profiles of Pennisetum giganteum - Jie Zhao; Zhao-Di Jing; Xue-Jing Yin; Jun-Feng Li; Zhi-Hao Dong; Si-Ran Wang; Tao Shao (Environmental Science and Pollution Research, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Glucose-responsive mesoporous prussian blue nanoprobes coated with ultrasmall gold and manganese dioxide for magnetic resonance imaging and enhanced antitumor therapy - Yuehua Shi; Yu Shi; Zhaoyang Wang; Jiahe Zhang; Ran Hao; Gangwan Zhang; Xiaolong Zhao; Leyong Zeng (Chemical Engineering Journal, 2023)

Depleted uranium causes renal mitochondrial dysfunction through the ETHE1/Nrf2 pathway - Suiyi Liu; Shuang Wang; Yazhen Zhao; Juan Li; Chang Shu; Yong Li; Jie Li; Binghui Lu; Zeheng Xu; Yonghong Ran; Yuhui Hao (Chemico-Biological Interactions, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Numerical simulation of dynamic responses of semi-rigid rockfall protection barriers subjected to impact loading at different positions - Xin Qi; Lei Zhao; Chao-Ran Hao; Zhi-Xiang Yu; Shi-Chun Zhao (Bulletin of Engineering Geology and the Environment, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

The effect and attributable risk of daily temperature on category C infectious diarrhea in Guangdong Province, China - Qiang Hao; Qi Gao; Ran Zhao; Haitao Wang; Hao Li; Baofa Jiang (Environmental Science and Pollution Research, 2022)

A methodology to determine the optimal quadrat size for desert vegetation surveying based on unmanned aerial vehicle (UAV) RGB photography - Mengyu Hao; Wenli Zhao; Longjun Qin; Peng Mao; Xu Qiu; Lijie Xu; Yu Jiu Xiong; Yili Ran; GuoYu Qiu (International Journal of Remote Sensing, 2021)

Cloning and functional identification of a strigolactone receptor gene MdD14 in apple - Yu-Ying Yang; Yi-Ran Ren; Peng-Fei Zheng; Ling-Ling Zhao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effect of LSU and ITS genetic markers and reference databases on analyses of fungal communities - Chao Xue; Yuewen Hao; Xiaowei Pu; C. Ryan Penton; Qiong Wang; Mengxin Zhao; Bangzhou Zhang; Wei Ran; Qiwei Huang; Qirong Shen; James M. Tiedje (Biology and Fertility of Soils, 2019)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Isolation and characterization of 18 microsatellite loci in the Chinese Noctule bat, Nyctalus plancyi - Hao Liu; Yujie Ran; Hongyan Shi; Xiaodong Jia; Lin Zhao (Conservation Genetics Resources, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Endothelium-specific SIRT1 overexpression inhibits hyperglycemia-induced upregulation of vascular cell senescence - HouZao Chen; YanZhen Wan; Shuang Zhou; YunBiao Lu; ZhuQin Zhang; Ran Zhang; Feng Chen; DeLong Hao; Xiang Zhao; ZhiChen Guo; DePei Liu; ChihChuan Liang (Science China Life Sciences, 2012)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)